When Experts Do Politics: Introducing Water Policy Reform in Brazil - Gutierrez, Ricardo Alberto (2010)
This article brings to the fore the role of experts as policy agents by analyzing the water management reform in three Brazilian states. Seeking to contribute to the recent ideational turn in political science, it contends that in studying the emergence and implementation of new policy ideas, more attention must be paid to the role of experts as policy innovators and to the interplay between experts' knowledge brokerage and the influence of party politics. To examine the interaction between knowledge brokerage and party politics, comparative case studies were conducted to trace back throughout their different phases the reform processes of the Brazilian states of Ceará, Paraná, and Rio Grande do Sul. The purpose of this research design is to test the argument that experts are major reform agents and that what experts can effectively achieve depends on both the reform phase and the political context they find themselves in. © 2010 Wiley Periodicals, Inc.